The Influence of Raw Material Quality and Production Process on Product Quality in Rigis Village Coffee Powder Brand Coffee Business in West Lampung Regency - Yoka Aman Saputra; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to examine and analyze the influence of raw material quality and production process on product quality in the Rigis brand coffee powder business in Kampung Kopi, West Lampung Regency. Raw material quality, primarily referring to the quality of coffee beans used in production, is considered a key factor in shaping the distinctive characteristics of coffee powder. Additionally, the production process involving various stages, such as roasting and grinding, is also believed to play a significant role in determining the final product quality. This case study is conducted to provide a deeper understanding of the interaction between raw material quality, production process, and product quality in the local coffee industry. The research method involves surveys with data collection through questionnaires and interviews with business owners and relevant stakeholders. Data analysis is conducted using regression techniques to test the influence of raw material quality and production process on the product quality of Rigis brand coffee powder. The results of this study indicate an influence of both raw material quality and production process on product quality.